Medication-Related Osteonecrosis of the Jaw: New Insights into Molecular Mechanisms and Cellular Therapeutic Approaches - Thomas Lombard; Virginie Neirinckx; Bernard Rogister; Yves Gilon; Sabine Wislet (Stem Cells International)
In recent years, medication-related osteonecrosis of the jaw (MRONJ) became an arising disease due to the important antiresorptive drug prescriptions to treat oncologic and osteoporotic patients, as well as the use of new antiangiogenic drugs such as VEGF antagonist. So far, MRONJ physiopathogenesis still remains unclear. Aiming to better understand MRONJ physiopathology, the first objective of this review would be to highlight major molecular mechanisms that are known to be involved in bone formation and remodeling. Recent development in MRONJ pharmacological treatments showed good results; however, those treatments are not curative and could have major side effects. In parallel to pharmacological treatments, MSC grafts appeared to be beneficial in the treatment of MRONJ, in multiple aspects: (1) recruitment and stimulation of local or regional endogenous cells to differentiate into osteoblasts and thus bone formation, (2) beneficial impact on bone remodeling, and (3) immune-modulatory properties that decrease inflammation. In this context, the second objective of this manuscript would be to summarize the molecular regulatory events controlling osteogenic differentiation, bone remodeling, and osteoimmunology and potential beneficial effects of MSC related to those aspects, in order to apprehend MRONJ and to develop new therapeutic approaches.